A mild acetolysis procedure for the regioselective removal of isopropylidene in di-O-isopropylidene-protected pyranoside systems. (5th June 2017) - Zhang, Pengfei; Ling, Chang-Chun
Abstract: A mild acetolysis method for the regioselective removal of isopropylidene group from di- O -isopropylidene-protected hexopyranosides is reported. O -Isopropylidene-protected intermediates play an important role in carbohydrate chemistry, as they are often found in commercially available furanosyl and pyranosyl materials, and some of them contain more than one O -isopropylidene groups. Methods that permit regioselective removal of O -isopropylidene groups are extremely valuable, as the number of steps in the total synthesis of complex oligosaccharides could be significantly decreased. Here we report that trifluoroacetic acid (TFA)/acetic anhydride (Ac2 O) can be used to regioselectively convert one of the two O -isopropylidene groups to vicinal di- O -acetates in the di- O -isopropylidene-protected galacto - and fructo -pyranosyl systems, and the reagent is compatible with some common functionalities such as sulfonate esters, bromide, azide etc. Graphical abstract: Highlights: Di- O -isopropylidene-protected hexopyranose systems can be regioselectively acetolyzed. Acetic anhydride-TFA can be used as a mild condition. The method is compatible with commonly used functionalities. Elaborately protected galactopyranosyl and fructopyranosyl intermediates can be synthesized in short reaction sequence.